Insights into the mechanism by which atropine inhibits myopia: evidence against cholinergic hyperactivity and modulation of dopamine release. (10th October 2021) - Thomson, Kate; Kelly, Tamsin; Karouta, Cindy; Morgan, Ian; Ashby, Regan
Abstract : Background and Purpose: The ability of the muscarinic cholinergic antagonist atropine to inhibit myopia development in humans and animal models would suggest that cholinergic hyperactivity may underlie myopic growth. To test this, we investigated whether cholinergic agonists accelerate ocular growth rates in chickens. Furthermore, we investigated whether atropine alters ocular growth by downstream modulation of dopamine levels, a mechanism postulated to underlie its antimyopic effects. Experimental Approach: Muscarinic (muscarine and pilocarpine), nicotinic (nicotine) and non‐specific (oxotremorine and carbachol) cholinergic agonists were administered to chicks developing form‐deprivation myopia (FDM) or chicks that were otherwise untreated. Vitreal levels of dopamine and its primary metabolite 3, 4‐dihydroxyphenylacetic acid (DOPAC) were examined using mass spectrometry MS in form‐deprived chicks treated with atropine (360, 15 or 0.15 nmol). Further, we investigated whether dopamine antagonists block atropine's antimyopic effects. Key Results: Unexpectedly, administration of each cholinergic agonist inhibited FDM but did not affect normal ocular development. Atropine only affected dopamine and DOPAC levels at its highest dose. Dopamine antagonists did not alter the antimyopia effects of atropine. Conclusion and Implications: Muscarinic, nicotinic and non‐specific cholinergic agonists inhibited FDM development. This indicates that cholinergic hyperactivity does not underlie myopic growth and questions whether atropine inhibits myopia via cholinergic antagonism. This study also demonstrates that changes in retinal dopamine release are not required for atropine's antimyopic effects. Finally, nicotinic agonists may represent a novel and more targeted approach for the cholinergic control of myopia as they are unlikely to cause the anterior segment side effects associated with muscarinic treatment.